Pendekatan Konseling Berbasis Mindfulness dalam Menurunkan Kecemasan Akademik Siswa - Della Dornauli Simanjuntak; Tria Yunita; Risma Anita Puriani (Lembaga Pengembangan Kinerja Dosen, 2026)
Academic anxiety is one of the problems commonly experienced by students due to the pressure of assignments, demands for achievement, and concerns about learning outcomes. This article aims to examine the effectiveness of mindfulness-based counseling in reducing students' academic anxiety and to explain the strategic role of guidance counselors in its application in schools. This study uses a literature review method with a literature review approach. Data were obtained from various national journals relevant to the topics of academic anxiety and mindfulness, then analyzed descriptively and qualitatively through a process of collecting, classifying, and synthesizing the results of previous studies. The results of the study show that mindfulness-based counseling is effective in helping students reduce their levels of academic anxiety through conscious breathing exercises, focusing attention, and accepting learning experiences without negative judgment. In addition, guidance counselors play an important role as facilitators, program developers, role models for mindfulness practices, mental health advocates, and liaisons between schools and parents in supporting the success of interventions. By applying the right methods, mindfulness-based counseling can be an effective alternative service in helping students overcome academic anxiety when implemented systematically and continuously by guidance counselors in schools.